The Role of Wnt Signaling in Postnatal Tooth Root Development - Tokavanich, Nicha; Wein, Marc N.; English, Jeryl D.; Ono, Noriaki; Ono, Wanida (Frontiers in Dental Medicine, 2021)
Appropriate tooth root formation and tooth eruption are critical for achieving and maintaining good oral health and quality of life. Tooth eruption is the process through which teeth emerge from their intraosseous position to their functional position in the oral cavity. This temporo-spatial process occurs simultaneously with tooth root formation through a cascade of interactions between epithelial and adjoining mesenchymal cells. Here, we will review the role of the Wnt system in postnatal tooth root development. This signaling pathway orchestrates the process of tooth root formation and tooth eruption in conjunction with several other major signaling pathways. The Wnt signaling pathway is comprised of the canonical, or Wnt/-catenin, and the non-canonical signaling pathway. The expression of multiple Wnt ligands and their downstream transcription factors including -catenin is found in cells in the epithelia and mesenchyme starting from the initiation stage of tooth development. Inhibition of canonical Wnt signaling in early stage arrests odontogenesis. Wnt transcription factors continue to be present in the dental follicle cells, the progenitor cells responsible for differentiation into cells constituting the tooth root and the periodontal tissue apparatus. This expression occurs concurrently with osteogenesis and cementogenesis. Conditional ablation of -catenin in osteoblast and odontoblast causes malformation of root dentin and cementum. On the contrary, overexpression of -catenin led to shorter molar roots with thin and hypomineralized dentin, along with failure of tooth eruption. Therefore, the proper expression of Wnt signaling during dental development is crucial for regulating the proliferation, differentiation, as well as the epithelial-mesenchymal interaction essential for tooth root formation and tooth eruption.